Corporate Records Retention, Volume 3, A Guide to Requirements of State Governments of the U.S. (Book). - Koch, Alfred P. (The Accounting Review, 1961)
Reviews the book "Corporate Records Retention: A Guide to Requirements of State Governments of the U. S."